ChemInform Abstract: Organocatalytic, Highly Enantioselective Vinylogous Mukaiyama—Michael Reaction of Acyclic Dienol Silyl Ethers. Issue 19 (18th April 2013) - Gupta, Vaishali; Sudhir V., Sai; Mandal, Tanmay; Schneider, Christoph
Abstract This reaction is accomplished for the first time.